The Impact on Brand Image Based on the Consumer Perception in Mobile Phone Industry: A Case Study on OPPO Smartphone (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2024)
The study aims to investigate the impact of brand image and Product Quality Performance of Oppo smartphones. The main objective of the study was to analyze the effect of product quality preference by consumers. This type of research uses a quantitative approach and multiple techniques were used for data analysis in this research. The population of this research is the citizens of Bangladesh who knows and using the smartphone Oppo products. A sample of this research is 150 respondents using the purposive sampling method. The various regression analyses were used in testing hypothesis. SPSS was used for the data -analyzing purpose in this research. The research has indicated that Brand image significantly effects Oppo Telecom performance and quality of products too. Basically research is prepared on the basis of practical observation and determines whether brand image could have a significant impact on the smartphone’s service at OPPO Mobile Company Ltd. This research was developed to learn about the practical scenario of a Telecommunications Company. These papers were conducted to find out the branding strategy of OPPO mobile performance in the telecom industry.